Large-scale synthesis of WO 3 nanoplates by a microwave-hydrothermal method - Sungpanich J. (2014)
Tungsten oxide (WO 3) nanoplates were synthesized by a 270 W microwave-hydrothermal reaction of Na 2WO 4·2H 2O and citric acid (C 6H 8O 7· H 2O) in deionized water. X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), and selected area electron diffraction (SAED) were used to reveal the synthesis of WO 3 complete rectangular nanoplates in the solution of 0.2 g citric acid for 180 min, with O-W-O FTIR stretching modes at 819 and 741 cm -1, and two prominent O-W-O Raman stretching modes at 804 and 713 cm -1. The 2.71 eV indirect energy gap, and 430-460 nm blue emission wavelength range of WO 3 complete rectangular nanoplates were determined using UV-visible and photoluminescence (PL) spectrometers. The formation mechanism was also proposed according to the experimental results. © 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.